2014
DOI: 10.1155/2014/513641
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Commercial Saturated Monoglyceride, Mono-/Diglycerides Mixtures, Vegetable Oil, Stirring Speed, and Temperature on the Physical Properties of Organogels

Abstract: The objective of this study was to evaluate the influence of gelator, vegetable oil, stirring speed, and temperature on the physical properties of obtained organogels. They were prepared under varying independent conditions and applying a fractional experimental design. From there a rheological characterization was developed. The physical characterization also included polarized light microscopy and calorimetric analysis. Once these data were obtained, X-Ray diffraction was applied to selected samples and a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…The microphotographs of polarized light microscopy (PLM) acquired for OG7, OG9, OG10, and OG12 are shown in Figure . Needle‐like crystals were revealed in PLM microphotographs similar to the results observed by Kesselman and Shimoni () in commercial MG crystallized in olive oil at 25°C by Ojijo, Kesselman, et al (); Co, and Marangoni, (); Rocha‐Amador et al () and Da Pieve, Calligaris, Eco, Nicoli, and Marangoni (). Also, Sintang et al () mentioned that MGs cluster as crystal aggregates along with one‐dimensional needle crystals and spherulite crystallites in OGs can be obtained by using different sources such as structurants at 10% concentration.…”
Section: Resultssupporting
confidence: 83%
“…The microphotographs of polarized light microscopy (PLM) acquired for OG7, OG9, OG10, and OG12 are shown in Figure . Needle‐like crystals were revealed in PLM microphotographs similar to the results observed by Kesselman and Shimoni () in commercial MG crystallized in olive oil at 25°C by Ojijo, Kesselman, et al (); Co, and Marangoni, (); Rocha‐Amador et al () and Da Pieve, Calligaris, Eco, Nicoli, and Marangoni (). Also, Sintang et al () mentioned that MGs cluster as crystal aggregates along with one‐dimensional needle crystals and spherulite crystallites in OGs can be obtained by using different sources such as structurants at 10% concentration.…”
Section: Resultssupporting
confidence: 83%
“…MG have shown their great potential to be used for a wide range of applications because they are able to crystallize and form a strong network with good elastic properties and high oil retention even when used at low concentrations (<10 wt%) (Da Pieve et al, 2010;. Studies described above agree upon the fact that the rheological, textural, and thermal properties of oleogels are greatly affected by the crystallization behavior of the MG, which in turn is driven by the type of oil and processing conditions such as agitation, concentration, temperature, and cooling rate (Giacomozzi, Carrín, & Palla, 2018;Rocha-Amador et al, 2014). According to , high cooling rates lead to lower elastic modulus values but harder networks at initial time.…”
Section: Introductionmentioning
confidence: 65%
“…On the other hand, studies done by different research groups had shown that the crystallization behavior of vegetable waxes (i.e., crystal size and shape) and further development of the crystal network are affected by other components, naturally present in the wax or intentionally added (Toro-Vazquez et al, 2007;Dassanayake et al, 2009;Morales-Rueda et al, 2009;Chopin-Doroteo et al, 2011;Blake et al, 2014;Hwang et al, 2014;Rocha-Amador et al, 2014). Monoglycerides are a minor component commonly present in refined vegetable oils at low concentrations commonly between 0.05 and 0.2% (Gunstone, 2002).…”
Section: Introductionmentioning
confidence: 99%